2022
DOI: 10.3390/jcm11206215
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Synovial Fistula of the Ankle Joint: A Case Series

Abstract: (1) Background: Little is known about the etiology, clinical features, diagnosis methods, treatments, and the prognosis of synovial fistula of the ankle joint. The purpose of this study is to investigate the clinical features of synovial fistula of the ankle joint. (2) Methods: Between March 2003 and December 2018, 40 cysts associated with synovial fistula of the ankle joint were treated consecutively by two surgeons. Case histories, clinical manifestations, intraoperative findings, surgical treatment methods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Several flaps have been used to cover the soft tissue defect that results after debridement of infected lateral malleolar bursitis. Park et al [1] and Kim et al [2] have reported successful outcomes of reverse sural artery flaps in infected lateral bursitis. Infected lateral malleolar bursitis often occurs as a diabetic complication [2].…”
Section: Introductionmentioning
confidence: 99%
“…Several flaps have been used to cover the soft tissue defect that results after debridement of infected lateral malleolar bursitis. Park et al [1] and Kim et al [2] have reported successful outcomes of reverse sural artery flaps in infected lateral bursitis. Infected lateral malleolar bursitis often occurs as a diabetic complication [2].…”
Section: Introductionmentioning
confidence: 99%